Biomechanical performance of the novel assembled uncovertebral joint fusion cage in single-level anterior cervical discectomy and fusion: A finite element analysis - Zhang, Xiang; Yang, Yi; Shen, Yi-Wei; Zhang, Ke-Rui; Ma, Li-Tai; Ding, Chen; Wang, Bei-Yu; Meng, Yang; Liu, Hao (Frontiers in Bioengineering and Biotechnology, 2023)
Abstract Introduction: Anterior cervical discectomy and fusion (ACDF) has been wildly accepted as the gold standard surgical procedure in the treatment of cervical radiculopathy and myelopathy. However, there is concern about the low fusion rate in the early period after ACDF surgery using the Zero-P fusion cage. To improve the fusion rate and solve the implantation difficulties, we creatively designed an assembled uncoupled joint fusion device. The aim of this study was to assess the biomechanical performance of the assembled uncovertebral joint fusion cage in single-level ACDF and compare it with the Zero-P device. Methods: A three-dimensional finite element (FE) of a healthy cervical spine (C2−C7) was constructed and validated. In the one-level surgery model, either an assembled uncovertebral joint fusion cage or a zero-profile device was implanted at the C5–C6 segment of the model. A pure moment of 1.0 Nm combined with a follower load of 75 N was imposed on C2 to determine the flexion, extension, lateral bending, and axial rotation. The segmental range of motion (ROM), facet contact force (FCF), maximum intradiscal pressure (IDP), and screw-bone stress were determined and compared with those of the zero-profile device. Results: The ROMs of the fused levels in both models were nearly zero, while the motion contributions of the unfused segments were unevenly increased. The FCF at adjacent segments in assembled uncovertebral joint fusion cage group was less than that of the Zero-P group. The IDP at adjacent segments and screw-bone stress was slightly higher in the assembled uncovertebral joint fusion cage group than that in the Zero-P group. Stress on the cage was mainly concentrated in the wings on both sides, reaching 13.4-20.4Mpa in the assembled uncovertebral joint fusion cage group. Conclusions: The assemble uncovertebral joint fusion cage provide strong immobilization similar to the Zero-P device. Compared with the Zero-P group, the assembled uncovertebral joint fusion cage achieved similar resultant values regarding FCF, IDP, and screw-bone stress. Moreover, the assembled uncovertebral joint fusion cage is effective for achieving early bone formation and fusion, probably due to the proper concentration of stress concentration in the wings on both sides.